Executive stress and burnout syndrome: focus on clinical lecturers in Nigerian - Solomon, Enyidah Nonyenim; Esther Ijeoma, Nonye-Enyidah; Dike, Alikor Chizindu; N., Elenwo Solomon (International Journal of Advances in Medicine, 2024)
The clinical lecturers are academic staff of the faculties of clinical sciences in the universities. They are all executives at all levels. Their duties in the hospitals and the university keep all the stress pathways always activated in them, making them easy preys to executive stress. The major cause of stress in executives are work related in 65%, family related in about 44%, young age and reduce physical activities. The standard workload formula (SWF) and the course credit system (CCS) currently used in Nigeria and by the universities all over the world to assign, measure, monitor and remunerate staff are not applicable in this faculty, leaving the members in state of learned helplessness. Academic burnout occurs when the academic work and home life become overwhelmingly unbearable. They currently have the highest prevalence rates in most disorders hence the need for urgent attention and reconsideration of the faculty policies.